METHODS FOR FINDING KEY POINTS IN AMBER SAMPLE IMAGES AS A BASIS FOR THREE-DIMENSIONAL MODELING - Ryzhuk, Andrii (European Science, 2025)
The paper considers an approach to three-dimensional visualization and modeling of amber samples to assess their shape, inclusions, color, and volume with subsequent industrial interpretation of the results. The obtained 3D data allow for the evaluation o